Thailand-World Bank Group Country Partnership Framework 2019-2022 - World Bank Group (World Bank, Bangkok, 2018)
The country partnership framework (CPF) for Thailand covers the period FY19-22. Guided by the Maximizing Financing for Development (MFD) principles, the CPF will bring to bear the full resources of the WBG to facilitate increased private sector-led development. To this end, the CPF will aim to create markets and increase private sector investment. To help create markets, the WBG will promote competition and innovation, and help open new markets by supporting improvements in Thailand’s business environment. Supporting the development of a stronger enabling environment will help increase private sector investment. Strengthening of fiscal institutions will also help create a more conducive national business environment that crowds in greater commercial financing and maximizes the impact of scarce public resources. The CPF will also support targeted policies and programs for the inclusion of disadvantaged and vulnerable groups, including in the fragile, conflict affected areas of Southern Thailand. The overarching goal of the CPF is to support Thailand’s transformation towards an innovative, inclusive and sustainable economy, which is aligned to the country’s first 20-Year National Strategy (2017-2036), the Royal Thai Government’s 12th NESDP (NESDP 12) as well as the WBG Systematic Country Diagnostic (SCD) – Getting Back on Track. The CPF envisages a partnership with Thailand focused on the provision of IBRD reimbursable and trust-funded Advisory Services and Analytics (ASA) targeting poverty reduction and shared prosperity with an option of IBRD financing based on Government demand, overall performance, as well as global economic/financial developments affecting IBRD’s financing capacity, and demand by other borrowers. The CPF plans to achieve six objectives that together aim at Promoting Resilient and Sustainable Growth, and Strengthening Inclusion. In particular, these objectives are i) to improve Thailand’s competitiveness and ease of doing business; ii) to improve financial and fiscal institutions’ policy implementation; iii) to strengthen the quality of infrastructure investments; iv) to address climate change and improve water resource management; v) to strengthen the social protection and inclusion of vulnerable groups; and vi) to promote quality education for all and talent management.